Determinination Of Iron, Potassium, Calcium, And Sodium In The Fruit Of Guava (Syzygium Aqueum) And Guava Semarang (SyzygiumSamarangense) In Spectrophotometry Atomic Absorpti - Syahputri, Hindri; De Lux Putra, Effendy; Rahman Harun, Fathur (Publisher Cv. Inara, 2023)
Syzygium belongs to the guava tribe or Myrtaceae, originating from Southeast Asia. Syzygium is divided into two: small water guava known as Syzygium aqueum and large water guava known as Syzygium samarangense. This study aims to determine the mineral levels of iron, potassium, calcium, and sodium contained in guava and guava Semarang and to compare mineral levels between a guava and guava Semarang. Each sample was dry digested, and then quantitative analysis of iron, potassium, calcium, and sodium was carried out using atomic absorption spectrophotometry (AAS) with a wavelength of 248.3 nm; potassium 766.5 nm; calcium 422.7; and sodium 589.0 nm. The advantage of this method is that it can determine the content of minerals in small quantities without being influenced by other minerals. The results showed the levels of iron, potassium, calcium, and sodium in guava and guava Semarang, respectively: (0.2553 ± 0.0077) mg/100g and (0.1548 ± 0.0152) mg/100g; (70.2326 ± 1.5738) mg/100g and (45.7714 ± 0.9827) mg/100g; (3.8588 ± 0.1619) mg/100g and (0.4663 ± 0.0507) mg/100g; (8.1187 ± 0.3375) mg/100g and (6.1648 ± 0.1689) mg/100g. A comparison of mineral content between guava and guava Semarang shows that iron, potassium, calcium, and sodium minerals in guava are more significant than in guava Semarang. Statistically, the different tests of the average content of iron, potassium, calcium, and sodium between guava and guava Semarang using the F distribution found that the content of iron, potassium, calcium, and calcium sodium in guava was significantly higher than in guava Semarang.